PEMBUATAN VIDEO COMPANY PROFILE DAN PRODUK MULTIMEDIA UNTUK SOSIAL MEDIA RUMAH SAKIT HEWAN PENDIDIKAN (RSHP) IPB: Creating Company Profile Video and Multimedia Product for Animal Hospital for Education (RSHP) IPB’s Social Media - Inna Novianty; Nurul Ulfa Ashilah; Arni Diana Fitri (IPB University, 2021)
ABSTRACTVarious interesting activities and facilities have been carried out at RSHP IPB, but these activities have not been packaged and disseminated attractively resulting in a lack of information received by the society. Companies can disseminate information moreinteresting and easy to understand to the target according to the goals to be achieved by implementing multimedia. Animal Hospital for Education of IPB uses video and motion graphic as a promotional forum to introduce RSHP IPB and expand the information the public will receive. The methods used in the manufacture of company profile video and multimedia product are briefing, idea construction, audiens target, device application determining, reference process, revision and publication.The result of this projects are a company profile video and multimedia product such as motion graphic.This products were shared at RSHP IPB’s Social Media.